Gender Transformative Methodologies CoP. Masculinities conversation 2 - Engaging men for gender equality in Uganda: Navigating resistance and backlash - Kodwo Mensah, Emmanuel; Mwiine, Amon; Bailey, Arwen (2024)
"Achieving gender equality requires the engagement of women and men, girls, and boys. It is everyone’s responsibility”. – Ban Ki-moon.